Custo-efetividade dos regimes imunossupressores utilizados na manutenção do transplante renal: coorte de dezesseis anos no Sistema Único de Saúde - Rosângela Maria Gomes (2020)
Introduction: In Brazil, Unified Health System is universal and responsible for ninety-five percent of all kidney transplants. The immunosuppressive regimens required after transplantation consist of a corticosteroid, a calcineurin inhibitor (cyclosporine or tacrolimus), an antiproliferative agent (azathioprine or mycophenolate mofetil), and sirolimus or everolimus. Objectives: The objective of this thesis was to compared the cost-effectiveness of therapeutic regimens used in the maintenance of kidney transplantation in SUS. Methods: Open historical cohort from 2000 to 2015, involving 44,795 kidney transplant patients by SUS in Brazil, constructed through deterministic-probabilistic matching of databases of the SUS. Article-1 analysis of the survival of renal graft of patients was performed. Patients who underwent kidney transplantation in SUS. The cumulative probability of survival was estimated by Kaplan-Meier. Potential factors associated with graft loss were assessed by univariate and multivariate analyzes using the Cox model. Article-2 the effectiveness analysis of treatment regimes containing CNI after kidney transplantation. Effectiveness was established by patient survival assessed by the KaplanMeier method. The patients were matched (1: 1). Article-3 has performed a cost-effectiveness evaluation in SUS perspective, carried out from data from the historical cohort from 2000 to 2015, with 2,318 patients who underwent kidney transplantation and who used CNI. Results: The renal graft survival rate was 91.2%, 77.0%, 57.5% and 42.1% for one, five, ten and 15 years respectively. Most of the patients were men, who underwent organ transplant from deceased donors and median age of 42 years. Higher risk of graft loss was associated with deceased donor organ (HR = 1.63; 95% CI 1.55 - 1.73), additional years of age (1.013; 1.011 -1.015), patients of black skin color (1.54; = 1,390 - 1.710), longer dialysis time prior to transplantation (1.203; 1.112 -1.268), primary diagnosis of diabetes mellitus (1.206; 1.089 -1.336), arterial hypertension (1.118, 1.114 -1.259) and mycophenolate regimens. The effectiveness assessment after paired analysis included 2,318 patients and demonstrated a higher risk of graft loss in patients using tacrolimus plus mycophenolate (2.17; 1.02-2.241) compared to those treated with cyclosporine plus azathioprine. The cost-effectiveness assessment showed that cyclosporine plus azathioprine demonstrated to be more cost effective compared to other regimens. Conclusions: The economic evaluation showed that the cyclosporine plus azathioprine regimen was cost effective than the other regimens evaluated. These findings can be useful to guide policy makers and prescribers in clinical practice.